Vishniacozyma changhuana sp. nov., and Vishniacozyma taiwanica sp. nov., two novel yeast species isolated from mangrove forests in Taiwan. Issue 3 (10th March 2021) - Chang, Chin-Feng; Huang, Sing-Yii; Lee, Ching-Fu
Abstract : Mangroves grow in the intertidal zone, which alternates between fresh water and sea water, with abundant bioresources. In mangrove habitats, yeasts play an important role in the decomposition of organic matter, and such nutrient cycling has high ecological importance. During a study of the diversity of yeast from Taiwan mangroves, seven strains of basidiomycetous yeasts were isolated and these yeasts represent two novel yeast species belonging to the genus Vishniacozyma . According to the sequences of the D1/D2 domain of large subunit (LSU) rRNA and the internal transcribed spacer (ITS) region, these seven strains could be clearly classified into two groups representing two individual, distinct species. Strains HM5L06, HM6L07, HM11L11 and BJ3S01, differed from their closest relative species Vishniacozyma phoenicis by 4–5 nt substitutions (no gaps) in the sequences of the D1/D2 domain of LSU rRNA and by 23 nt substitutions (10 gaps) in the ITS region. Strains HM6L11, HM7L02 and HM8L19, differed from their closest relative species Vishniacozyma penaeus by 7 nt substitutions (one gap) in the sequences of the D1/D2 domain of LSU rRNA and by 27 nt substitutions (12 gaps) in the ITS region. The scientific names of Vishniacozyma taiwanica sp. nov. and Vishniacozyma changhuana sp. nov. are proposed for these strains. The holotypes are Vishniacozyma taiwanica BCRC 23477 T (ex-type HM5L06=CBS 16558; MycoBank number MB837428) and Vishniacozyma changhuana BCRC 23478 T (ex-type HM6L11=CBS 16556; MycoBank number MB837429).